PENGGUNAAN MEDIA POP-UP BOOK UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KERAGAMAN BUDAYA DAERAH DI KELAS V SD INPRES PERUMNAS 1 - Rido, Debrina Eunike; Taty R. Koroh; Martha Khristina Kota (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This classroom action research aimed to improve students’ learning outcomes on the topic of regional cultural diversity through the use of Pop-Up Book media in Grade V of SD Inpres Perumnas 1 Kota Kupang. The problem identified in this study was the low learning outcomes of students caused by teacher-centered instruction and limited use of innovative learning media. The objective of this study was to enhance students’ learning outcomes through the implementation of Pop-Up Book media. This research used Classroom Action Research (CAR) consisting of two cycles, each including planning, action, observation, and reflection. The subjects were 20 fifth-grade students. Data were collected through learning outcome tests and observation sheets of teacher and student activities. The results showed that the implementation of Pop-Up Book media significantly improved students’ learning outcomes. The average score increased from 63.25 with 45% mastery in Cycle I to 80.75 with 90% mastery in Cycle II. In addition, teacher and student activities also improved from the “fair” category in Cycle I to the “very good” and “good” categories in Cycle II. These findings indicate that Pop-Up Book media is effective in improving students’ understanding, learning motivation, and learning outcomes in cultural diversity material.